Use Of ICT In Teaching Vocational Subjects - Banagiri, Richa; Kumar, Anuj; Pandey, Anoop (International journal of education and development using information and communication technology, 2021)
In today's modern world, globalization has completely changed the way of working. How we live, learn, work, and even define work has changed due to new information and communication technologies. It can be stated that human capital fuels the modern economy, but in reality, the information and communication technology revolution has turned intelligence into a valuable commodity. In today's economy, economic growth is based on mental intelligence rather than physical strength, and its worth is generated by recruiting knowledgeable workers and continuing to learn. Therefore, incorporating information and communication technology (ICT) into vocational and technical education and the educational system has a vast range of consequences for teaching and learning. ICT has enormous potential in developing vocational and professional teaching and learning content. Therefore educators have to be mindful in incorporating ICT into the educational transfer framework. However, this may result in typical guidance problems that come with reform, as it is, after all, an invention. Therefore, educators must be able to balance the advantages and disadvantages of embracing ICT as a tool.